2015
DOI: 10.1002/syn.21802
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stromal cells transplantation combined with ultrashortwave therapy promotes functional recovery on spinal cord injury in rats

Abstract: This study investigated the effects of bone marrow stromal cells (BMSCs) transplantation combined with low dose ultrashortwave (USW) radiation on functional recovery from spinal cord injury (SCI) in rats. Female Sprague-Dawley rats (n = 64) were randomly divided into five groups: sham-operated, as well as control, USW, BMSCs, and BMSCs + USW that were subjected to spinal cord contusion. BMSCs were transplanted into rats in the BMSCs and BMSCs+USW groups, while those in the USW and BMSCs + USW were exposed to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…The ratio of the cavity area in the spinal cord cross-sectional area by HE staining was calculated somewhat, to histologically show the function of the spinal cord [28,29]. Severe damage of the dorsal white matter and central grey matter was observed in SCI rats when compared with the sham group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of the cavity area in the spinal cord cross-sectional area by HE staining was calculated somewhat, to histologically show the function of the spinal cord [28,29]. Severe damage of the dorsal white matter and central grey matter was observed in SCI rats when compared with the sham group.…”
Section: Resultsmentioning
confidence: 99%
“…According to reports in the literature, the apoptosis of neurons, oligodendrocytes, astrocytes, and microglia cells in tissues from injured segments and adjacent segments from 4 hr to 3 weeks could be observed after SCI [30,31,32]. The apoptosis of spinal cord neurons caused the impairment and loss of spinal cord sensory and motor functions [29]. Consistent with our findings, it is known that trauma and ischemia of the spinal cord can cause neuronal apoptosis, which could be attenuated by DG treatment in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…All the procedures were carried out as described . In brief, Total RNA was extracted by TRIzol (Invitrogen) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…[76][77][78][79] There is a large body of evidence demonstrating that the effects of MSCs on macrophages are critical for inflammatory response and tissue repair after SCI. [80][81][82][83][84] Nakajima et al observed that BM-MSCs altered macrophages into anti-inflammatory M2 and beneficially modulated the immune system. 80 When human BM-derived macrophages were cocultured with human BM-MSCs, these macrophages showed high expression of a well-known marker of alternatively activated M2 macrophages (CD206) and expressed low levels of TNF-α and IL-12 and high levels of IL-6 and IL-10.…”
mentioning
confidence: 99%